Mind the Gap: Mismatches Between Clinicians and Patients in Heart Failure Medication Management - Chin, K.; Skiba, M.; Reid, Christopher; Tonkin, A.; Hopper, I.; Mariani, J.; Liew, D. (2018)
© 2018 Springer Science+Business Media, LLC, part of Springer Nature Purpose: Previous studies on the ‘treatment gap’ in patients with heart failure (HF) have focused either on prescribing or patients’ adherence to prescribed treatment. This study sought to determine whether or not recent initiatives to close the gap have also minimised any mismatches between physicians’ expectation of their patients’ medications, medications in the patients’ possession and their actual medication use. Methods: A cross-sectional observational survey was conducted from December 2015 to June 2016 in The Alfred Hospital HF clinic in Melbourne, Australia. Patients were invited to participate if they had chronic HF (NYHA class II to IV), were aged = 60 years, had no history of HF related hospitalisation within the past 6 months and were prescribed at least two HF medications. Results: Of 123 eligible patients, 102 were recruited into the study. Beta-blockers, mineralocorticoid receptor antagonists, loop diuretics and statins were associated with the highest rates of mismatches of drugs and doses, ranging from 10 to 17%. Discrepancy of total daily doses was the most common type of mismatch. Overall, only 23.5% of the patients were taking the right drugs at the right doses as expected by their cardiologists/HF specialists. Conclusions: Despite improved prescribers’ adherence to guideline-directed medical therapy, there remain considerable mismatches between prescribers’ expectation of patients’ HF medications, medications in patients’ possession and their actual medication use. Initiatives to improve this situation are urgently needed.